PARTIAL-WAVE ANALYSIS OF BACKWARDLY PRODUCED 3-PION SYSTEMS IN K-P INTERACTIONS AT 4.2 GEV-C - Foster, B; Grossmann, P; Lamb, P; Mcdowell, W; Wells, J; Blokzijl, R; Wolters, G; Armenteros, R; Dionisi, C; Gavillet, P; Loverre, P; Mazzucato, M; et al. (1981)
We report on the results of a partial-wave analysis of the 3π system produced by baryon exchange in the reaction K-p→Σ-π+π+π- at 4.2 GeV/c. We confirm the existence of an enhancement in the 1+S(ρ{variant}π) wave as previously established from a Dalitz plot analysis of the same data. The phase variation of this wave is found to be consistent with that expected for a resonance and thus the enhancement is identified with A1 production. No clear signal for this state is found in either the reaction K-p→Σ+π+π+π-π- or K-p→Λπ+π-π0. We also find production via baryon exchange of the A2 in all three reactions and the ω and ω* (1975) in the third reaction. © 1981.